Semblanzas ictiológicas : Mariano González Castro - López, Hugo Luis (2013)
Fil: López, Hugo Luis. División Zoología Vertebrados. Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina